The Embodiment of Tri Hita Karana in the Awig-Awig of the Traditional Village of Tenganan Pegringsingan in the Period BEFORE Independence - Yowana, I Made Adiwidya; Noor, M.; Juniasa, I Dewa Nyoman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to examine the manifestation of Tri Hita Karana in the awig-awig of Tenganan Pegringsingan Customary Village during the pre-independence era. The type of research used in this study is legal research. The approach used is the statutory approach. Legal materials are analyzed qualitatively, meaning the data and facts found will be described. The results of the study show that the Awig-awig of Tenganan Pegringsingan Customary Village before the independence era had manifested the concept of Tri Hita Karana. This can be seen from the articles regulating the three elements of Tri Hita Karana, namely parahyangan, pawongan, and palemahan. There are four articles that regulate Parahyangan. Regulations regarding parahyangan include contributions during religious ceremonies and the obligation for newcomers to participate in religious ceremonies. Regarding the pawongan aspect, there are 22 articles related to human relations. Pawongan provisions among other things, it regulates meetings and the attire that must be worn, marriages, and inheritance. Furthermore, regarding the aspect of palemahan, there are 15 articles that regulate relationships with nature/environment. The regulation of palemahan includes village boundaries/territories, plants/trees that are allowed and not allowed to be planted, as well as sanctions for those who violate the rules. The embodiment of Tri Hita Karana in the awig-awig of Tenganan Pegringsingan Customary Village shows that the concept of Tri Hita Karana has been a norm since before independence.